Façades : Principles of Construction - Knaack, Ulrich; Auer, Thomas; Bilow, Marcel; Klein, Tillmann (Birkhäuser, 2014)
This book demonstrates the principles of facade construction. Guidelines are suggested for good detailing. The installation procedures are described for the most common materials – glass, wood, steel, concrete, and aluminum. Numerous drawings made specially for the book explain the principles of the individual types of facade which are then illustrated with built examples.